Development and application of HPLC-RI and HPLC-MS/MS based methods for quantification of residual deoxycholate levels in pneumococcal polysaccharides. Issue 6 (November 2016) - Gairola, Sunil; Gautam, Manish; Patil, Dada; Manoj Kumar, Krishna; Shinde, Pravin; Jana, S.K.; Dhere, Rajeev; Jadhav, Suresh
Abstract: The analysis of residual sodium deoxycholate (DOC); a detergent of biological origin used in manufacturing of polysaccharide vaccines is challenging due to complex sample matrices and the lack of suitable methods. Here we report, rapid and sensitive high-performance liquid chromatography-refractive index (HPLC-RI) and tandem mass spectrometry (HPLC-MS/MS) methods for estimation of residual DOC in pneumococcal polysaccharides. For HPLC-RI method, separation was achieved using Luna C18 column and mobile phase compositions of acetonitrile: methanol: 20 mM sodium acetate (60:05:35% v/v). For HPLC-MS/MS method, separation was achieved using a Hypersil BDS C18 column with gradient elution of methanol and water (0.1% formic acid). MS/MS method showed linearity (r 2  = 0.997) over the range of 10–320 ng/mL with limits of detection (LOD) and lower limit of quantitation (LOQ) of 3 and 10 ng/mL respectively. Precision (% RSD) and accuracy (% recovery) for both methods were in the range of 0.74–8.29% and 82.33–117.86% respectively. Sample matrices interferences were addressed following novel sample clean-up method based on liquid–liquid extraction. Both methods enabled traceable quantitation of DOC in intermediate and purified pneumococcal polysaccharides of serotypes: 1, 5, 6A, 6B, 7F, 9V, 14, 19A, 19F and 23F.